Meningkatkan Ketuntasan Belajar Siswa Materi Interaksi Mahluk Hidup dengan Lingkungan Menggunakan Model Problem Based Instruction - Riyanto, Winda; Hikamah, Siti Roudlotul; Nurjanah, Umi (FKIP Universitas Islam Jember, 2024)
The application of learning model innovative type the problem based instruction to improve ketuntasan to study for students to the matter interaction creatures with the environment ‘the application of learning model innovative type the problem based instruction to improve ketuntasan to study for students to the matter interaction creatures with the environment in MTs. Hasanuddin semboro jember. Based on the research done, so of students to study in the cycle i obtained the average 73,2 with ketuntasan klasikal 72 %, and on the average cycle ii diproleh 82,3 with klasikal 92 % , student learning ketuntasan has recorded an increase of 20 % .So that the result of students to study has increased very large thus learning activities model the problem of fee-based instruction student learningketuntasan managed to change for the better.